Activities of Art Organizations in the Conditions of the Russian-Ukrainian War on the Example of the Public Associations "Art Front" and "Art Sich" - Порядченко, Л.; Демчук, А.; Ятченко, А. (Київський національний університет імені Тараса Шевченка, 2025)
The relevance of the research. The full-scale invasion of Ukraine by the Russian Federation on 24 February 2022 became not only an existential challenge to statehood but also a catalyst for radical changes in the socio-cultural sphere. In the context of hybrid warfare, when the enemy is trying to destroy the cultural identity of a nation, art has taken on strategic importance. The activities of arts organisations have gone beyond their aesthetic functions, transforming into a powerful tool of national resistance and volunteerism. Public associations have played a special role in this process, as organisations that, thanks to their mobility, are able to respond quickly to the challenges of the times. To understand the mechanisms of self-organisation of society during the period of military operations on the territory of Ukraine, it is necessary to study the activities of such public organisations as the Art Front and Art Sich, which were created in 2022–2023 and aimed at supporting the morale of the people during the war. The purpose is to analyse the specifics of the activities of artistic organisations in wartime, using the example of the public associations ‘Art Front’ and ‘Art Sich’, and to determine their role in supporting the Armed Forces of Ukraine and preserving the national identity of citizens.Conclusions. Under martial law, there has been a radical change in the paradigm of artistic associations. The focus has shifted from aesthetic and entertainment functions to mobilisation, therapeutic, and volunteer functions. Art has become an instrument of national resistance, integrated into the overall state defence system. An analysis of the work of the Art Front and Art Sich NGOs has made it possible to identify two complementary models of cultural volunteering:“Mediadiplomacy” (Art Front): focused on large-scale actions, the use of digital platforms, working with an international audience and accumulating significant financial resources through online tools.“Field” (Mystetskyi Sich): focused on mobility, direct contact with military personnel on the front line, providing targeted assistance, and holding small-scale events in extreme conditions. The activities of these organisations have proven their effectiveness as "rapid psychological assistance." Cultural events in the combat zone and hospitals help reduce combat stress and maintain high morale among Ukrainian Armed Forces personnel.

Актуальність. Повномасштабне вторгнення РФ в Україну 24 лютого 2022 р. стало не лише екзистенційним викликом для державності, а й каталізатором докорінних змін саме у соціокультурній сфері. В умовах гібридної війни, коли ворог намагається знищити культурну ідентичність нації, мистецтво набуло стратегічного значення. Діяльність мистецьких організацій вийшла за межі естетичної функції, трансформувавшись у потужний інструмент національного спротиву та волонтерства. Особливу роль у цьому процесі стали відігравати громадські об’єднання – організації, які завдяки своїй мобільності здатні оперативно реагувати на виклики часу. Для розуміння механізмів самоорганізації суспільства в період воєнних дій на території України необхідним є дослідження діяльності таких громадських організацій, як «Мистецький фронт» та «Мистецька Січ», які були створені у 2022–2023 рр.  і спрямовані на підтримку морального духу людей під час війни. Мета – проаналізувати специфіку діяльності мистецьких організацій в умовах війни на прикладі громадських об’єднань «Мистецький фронт» і «Мистецька Січ», визначивши їхню роль у підтримці ЗСУ та збереженні національної ідентичності громадян. Висновки. В умовах воєнного стану відбулася докорінна зміна парадигми діяльності мистецьких об’єднань. Естетична та розважальна функції відійшли на другий план, поступившись місцем мобілізаційній, терапевтичній та волонтерській. Мистецтво стало інструментом національного спротиву, інтегрованим у загальну систему оборони держави. Аналіз роботи ГО «Мистецький фронт» та «Мистецька Січ» дав можливість виокремити дві комплементарні моделі культурного волонтерства: «Медійно-дипломатична» («Мистецький фронт»): орієнтована на масштабні акції, залучення цифрових платформ, роботу з міжнародною аудиторією та акумуляцію значних фінансових ресурсів через онлайн-інструменти. «Польова» («Мистецька Січ»): орієнтована на мобільність, безпосередній контакт із військовими на лінії зіткнення, надання адресної допомоги та проведення камерних заходів в екстремальних умовах. Діяльність зазначених організацій довела свою ефективність як засіб «швидкої психологічної допомоги». Культурні заходи в зоні бойових дій та шпиталях сприяють зниженню рівня бойового стресу та підтримці високого морального духу особового складу ЗСУ.
Діяльність мистецьких організацій в умовах російсько-української війни на прикладі громадських об’єднань «Мистецький фронт» і «Мистецька Січ»
Keywords: російсько-українська війна; мистецький фронт; культурна дипломатія; волонтерський рух; громадські організації; «Мистецький фронт»; «Мистецька Січ»; національна ідентичність; культурний спротив